PENGARUH STRATEGI JOYFUL LEARNING DAN ICE BREAKING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS 10 SMA NEGERI 41 JAKARTA - Hendro Prasetyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Joyful Learning and Ice Breaking strategies on the biology learning outcomes of 10th-grade students at SMA Negeri 41 Jakarta. The research method used was an experiment with a quasi-experimental design, a non-equivalent control group design. The study population was 10th-grade students at SMA Negeri 41 Jakarta, with a purposively selected sample of two classes. The research instrument was a multiple-choice biology learning outcome test. The results showed that: (1) the Joyful Learning strategy had a significant effect on student learning outcomes, and (2) the Ice Breaking strategy also had a significant effect on student learning outcomes, with an average score of 20.60% during the learning activities. The average score for students' biology learning activities in the observed components was 79.11%. The assessment of biology learning outcomes using daily tests and mid-term exams was 79.11%, representing an increase of approximately 30.57 points. Thus, the use of enjoyable and varied learning strategies significantly influences students' biology learning outcomes.